2012
DOI: 10.1002/hyp.9652
|View full text |Cite
|
Sign up to set email alerts
|

Using a novel tracing‐tracking framework to source fine‐grained sediment loss to watercourses at sub‐catchment scale

Abstract: Although traditional sediment tracing approaches provide valuable information for characterising key generic sediment sources, Catchment Officers working as part of the Catchment Sensitive Farming initiative frequently require more detailed evidence to permit improved targeting of mitigation. Accordingly, a novel framework combining conventional sediment source fingerprinting and a dual signature tracking method has recently been used to improve sediment source information for the River Glaven (~115 km 2 ) pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 54 publications
(65 reference statements)
0
38
0
Order By: Relevance
“…The final set of optimum fingerprinting properties is dependent on the ability of the composite signature to improve source discrimination. Previous studies have also reported similar variability in the number and combination of fingerprinting properties used in the final set of optimum fingerprinting properties at a subwatershed scale (e.g., Collins et al, 2010Collins et al, , 2013aSmith and Blake, 2014). Increasing the number of source samples within a subwatershed can help to address this issue.…”
Section: Statistical Analysesmentioning
confidence: 88%
“…The final set of optimum fingerprinting properties is dependent on the ability of the composite signature to improve source discrimination. Previous studies have also reported similar variability in the number and combination of fingerprinting properties used in the final set of optimum fingerprinting properties at a subwatershed scale (e.g., Collins et al, 2010Collins et al, , 2013aSmith and Blake, 2014). Increasing the number of source samples within a subwatershed can help to address this issue.…”
Section: Statistical Analysesmentioning
confidence: 88%
“…Martinez-Carreras et al, 2010b;Smith and Blake, 2014;Collins et al, 2013), though, discrimination of the soil sources with the fingerprinting procedure was possible for the alpine Benasque catchment because of its distinctive soil characteristics.…”
Section: Solid Earthmentioning
confidence: 99%
“…New methods of ascribing the source of fine-grained sediments from arable fields and river banks using fingerprinting approaches are now available and emphasise the importance of compacted areas such as wheelings [105].…”
Section: Off-site Effects Of Soil Erosionmentioning
confidence: 99%